Malaysian Firms’ Shareholders’ Wealth Effect Following Cross-Border Acquisition - Hasan, Md Mahadi; Ibrahim, Yusnidah; Olajide, Raji Jimoh; Minai, Mohd Sobri; Uddin, Md Mohan (2017)
Objective: Purpose of this study is to investigate long run shareholders’ wealth effect (SWE) of Malaysian acquiring firms following cross-border acquisition (CBA).Methodology: Using buy-and-hold abnormal returns model for shareholder’s wealth effect and Euclidean method for identifying matching firms, study was employed 176 CBA deals of Malaysian acquiring firms for period of 2004-2015.Using conventional t-statistics, skewness adjusted t-statistics, bootstrapping skewness adjusted t-statistics and Multivariate of Analysis of Variance (MANOVA) as statistical tools were analyzed the data and test the hypotheses that acquiring firms’ wealth effect is impacted by CBA deals. Results: Study found that shareholder wealth effect of acquiring firm is significantly positive in shorter period while negative or mixed effect in longer period due to use different method to measures.However, there is no difference of SWE between the groups: Level of control in target firm (including SWE of Major vs. Minor acquisitions) and SWE of Shariah-complaint status firms vs. conventional firms. Moreover, Shareholder’s wealth effect differ industry to industry.Implication: study presents an empirically supported to describe the significance of long run shareholder’s wealth effect of Malaysian acquiring firms following cross-border acquisition.Firstly, study focuses on long-run shareholders’ wealth effect of Malaysian acquiring firms rather than short-run shareholder effects. Secondly, it utilizes a long-run methodology commonly used in such events as domestic mergers, seasoned equity offerings, and IPOs (e.g. Fama, 1998), but not applied to cross-border acquisition.This paper is most extensive analysis to date of the long-run performance of Malaysian acquiring firms carrying out cross-border acquisitions.